ANALYSIS OF CAPITAL STRUCTURE AND WORKING CAPITAL IN PHARMACEUTICAL RETAIL COMPANIES - Pamian Siregar; Sri Hartoyo; Hendro Sasonko (Universitas Tidar, 2019)
In the retail business, there is a term retail is number. PT Kimia Farma Pharmacy roomates the biggest retail pharmacy chain in Indonesia established additional number of pharmacies stores (drugstore) as a competitive strategy since 2013. The funding source for investment in the addition of store pharmacies comes from internal cash and short-term bank loans ( debt), the resulting in a funding mismatch. Management of the capital structure do not good cause disruption of the operational activities in the short term and the composition of the capital structure inefficient. The company's operational performance was disrupted as indicated resources by the decline in financial activities starting ratios implemented a strategy in 2013 and the decline in operational cash flow starting in 2016, even negative in 2017. The calculation of the working capital requirement 2012-2017 show that the yearly available working capital is sufficient to finance working capital requirements within that particular period. The available working capital in 2017 could fulfill the requirement of working capital for 2018 sales targets. The liquidity was disrupted due to the Decrease in cash operation the caused by funding mismatches. The optimal capital structure simulation is a composition of 40% debt and 60% equity in 2017, the event in balance sheet composition of 69% debt and 31% equity. The liquidity was disrupted due to the Decrease in cash operation the caused by funding mismatches. The optimal capital structure simulation is a composition of 40% debt and 60% equity in 2017, the event in balance sheet composition of 69% debt and 31% equity. The liquidity was disrupted due to the Decrease in cash operation the caused by funding mismatches. The optimal capital structure simulation is a composition of 40% debt and 60% equity in 2017, the event in balance sheet composition of 69% debt and 31% equity.